Reciprocity in global social protection: providing care for migrants' children. (2nd January 2017) - Dankyi, Ernestina; Mazzucato, Valentina; Manuh, Takyiwaa
Abstract: Migration research tends to conceptualize migrants as providers of social protection for people back home. Yet the care conducted within transnational families and the way it is organized is an integral part of a global social protection system which is based on reciprocity between migrants and their families in their home countries. This system relies on the work of people back home just as much as on the remittances of migrants overseas. Drawing on ethnographic data from 34 caregivers, we provide a detailed description of the work conducted by people in Ghana to care for migrants' children and analyze what caregivers do to make this work possible. We find that caregivers have small networks of support they can rely on and identify the strategies they develop when remittances are not forthcoming or enough to cater for the material needs of migrants' children.